1991
DOI: 10.1002/cne.903140202
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic processing of vibrissal information in the rat. I. Afferent input to the medial ventral posterior and posterior nuclei

Abstract: Retrograde tracing with true blue (TB) and diamidino yellow (DY) and anterograde tracing with either wheatgerm agglutinin-conjugated horseradish peroxidase (WGA-HRP) or Phaseolus vulgaris leucoagglutinin (PHA-L) were employed to investigate the projections from trigeminal nucleus principalis (PrV) and trigeminal subnucleus interpolaris (SpI) to their targets in the medial ventral posterior (VPM) and posterior (POm) nuclei of the thalamus. Many more cells in both PrV and SpI were labeled by tracer injections in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 38 publications
10
82
3
Order By: Relevance
“…Consistent with a previous report (Deschenes et al 1998), inspection of the thalamus revealed large numbers of BDA- labeled fibers originating from POm that traversed the VPM en route to the DLS and cortex. In addition, we also observed retrogradely labeled neurons in the interpolaris and other spinal trigeminal nuclei, which is consistent with tracer injections in the POm (Chiaia et al 1991;Peschanski 1984).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with a previous report (Deschenes et al 1998), inspection of the thalamus revealed large numbers of BDA- labeled fibers originating from POm that traversed the VPM en route to the DLS and cortex. In addition, we also observed retrogradely labeled neurons in the interpolaris and other spinal trigeminal nuclei, which is consistent with tracer injections in the POm (Chiaia et al 1991;Peschanski 1984).…”
Section: Resultssupporting
confidence: 88%
“…Both POm and VPM process somesthetic information received from the trigeminal nuclei (Chiaia et al 1991;Peschanski 1984;Timofeeva et al 2004;Veinante et al 2000a). Consequently, either of these thalamic nuclei could transmit whisker-related information directly to the DLS.…”
Section: Resultsmentioning
confidence: 99%
“…Stimulus-induced correlations were minimized by application of a trial-by-trial shift predictor (Gerstein et al 1989), thus suggesting a common excitatory neural noise source driving VPM correlated activity. The most likely source of these noise-induced VPM correlations is spontaneous excitatory input from principal (PrV) trigeminal nucleus projections or spinal trigeminal nucleus (SpV) projections to VPM thalamus (Chiaia et al 1991;Friedberg et al 2004;Timofeeva et al 2004;Wang and Ohara 1993). Other well described circuit mechanisms could also produce noise correlations among VPM neurons including descending projections from the BF cortex (Bal et al 1995;Bal and McCormick 1996;Friedberg et al 2004;Harris 2005;Lampl et al 1999;Nicolelis et al 1995;Ritz and Sejnowski 1997;Singer 1999).…”
Section: Heterogeneity Of Effects On Target Neuronsmentioning
confidence: 99%
“…Moreover, convergent projections from either the principal (PrV) or spinal trigeminal nucleus (SpV) likely provide singular inputs to VPM neurons. For example, both anatomical and electrophysiological studies reveal SpV neurons have large receptive fields and project to PrV and VPM thalamus, thus eliciting responses in VPM neurons from several whiskers (Chiaia et al, 1991;Wang and Ohara, 1993;Friedberg et al, 2004;Timofeeva et al, 2004). Additionally, differences in response latencies between PrV (ϳ6.7 ms) or SpV (ϳ11 ms) and VPM neurons (Friedberg et al, 2004) could indeed produce the sharp and delayed peaks that were evident in many cross-correlegrams.…”
Section: Dynamic Reorganization Of the Neural Ensemblementioning
confidence: 99%